Cardiovascular Risk Factors in Obese Children and Adolescents: A Systematic Review - Azzini, Vitor Ohana Marques; Lopes, Cristianne Confessor Castilho; Beker, Natascha Szumsztajn; Lopes, Eduardo Barbosa; Lopes , Lucas Castilho; Lopes, Maria Eduarda Castilho; Pitanga , Fábio Herget; Filho, Mushue Dayan Hampel Vieira; Guimarães, Larissa Silva (Medical Research and Its Applications Vol. 4, 2024)
Introduction: Childhood obesity is a multifactorial problem, with causes include inadequate eating habits, lack of physical activity, genetic predisposition and environmental influences. Objective: Understand and analyze the factors that contribute to increased cardiovascular risks in children suffering from obesity. Methods: This study constitutes a systematic review, classified as exploratory and descriptive. The preparation of the research was a bibliographical search in electronic databases on methods associated with SLR (Systematic Literature Review) and the applications of SMARTER (Simple Multi-Attribute Rating Technique using Exploiting Rankings). Results: A comprehensive systematic search of the literature yielded a total of 5125 articles referring to the incidence of obesity and overweight in adolescents, of which 29 articles were eligible to be included in this systematic review. Conclusion: Investing in the cardiovascular health of obese children is investing in the future of a healthier and stronger population. By implementing effective preventive and intervention measures, we can help reduce the global burden of cardiovascular disease and create an environment where all children have the opportunity to achieve their full potential for health and well-being throughout their lives.